2021
DOI: 10.1177/24730114211026933
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing for Pathogen Identification in Infected Foot Ulcers

Abstract: Background: Accurate identification of primary pathogens in foot infections remains challenging due to the diverse microbiome. Conventional culture may show false-positive or false-negative growth, leading to ineffective postoperative antibiotic treatment. Next-generation sequencing (NGS) has been explored as an alternative to standard culture in orthopedic infections. NGS is highly sensitive and can detect an entire bacterial genome along with genes conferring antibiotic resistance in a given sample. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…36 In a study of infected foot ulcers, complete concordance of NGS and culture was found in 14 cases (46.7%), partial concordance in 8 cases (26.7%), and discordance in 8 cases (26.7%). 37 The 70% concordance rate in our study is similar to literature reports.…”
Section: Discussionsupporting
confidence: 91%
“…36 In a study of infected foot ulcers, complete concordance of NGS and culture was found in 14 cases (46.7%), partial concordance in 8 cases (26.7%), and discordance in 8 cases (26.7%). 37 The 70% concordance rate in our study is similar to literature reports.…”
Section: Discussionsupporting
confidence: 91%
“…[78][79][80][81][82] Our systematic review identified 4 recent single-centre prospective studies that compared the results of different non-culture (molecular microbiological) methods to those of conventional culture. 49,[83][84][85][86] These studies addressed this question in both skin and soft-tissue infections and osteomyelitis of the foot.…”
Section: Rationalementioning
confidence: 99%
“…82 The studies also confirmed that non-culture techniques, especially metagenomic next-generation sequencing (mNGS) (NGS), identify more bacteria from tissue samples, including bone, than conventional cultures. [83][84][85][86] Currently, the use of mNGS techniques does not lead to a shorter time until pathogen identification, but this might change with the deployment of newer techniques. These techniques may help choose the empirical antibiotic therapy and reduce the risk of inappropriate treatment (i.e., failing to cover bacteria involved, including multiresistant ones).…”
Section: Rationalementioning
confidence: 99%
“…Reverse Transcription Polymerase Chain reaction (qRT-PCR) 30 DNA sequencing, 32,33 16S ribosomal ribonucleic gene sequencing 34 and immunoassay. 31 Data about the coexistence of peripheral artery disease in the included patients and whether patients received antibiotics prior to tissue sampling (except in Choi's study 29 ) were not provided in these studies. Three studies [29][30][31] assessed mNGS in skin structure DFIs.…”
Section: Summary Of the Literaturementioning
confidence: 99%